Management of the Pre Pubertal Girls with Labial Adhesions - Paul, BJ; Das, CR (Journal of Nepalgunj Medical College, 2016)
Back ground: Pre pubertal labial adhesion is an important pediatric gynecological problem. Parents panic about this condition as absent vagina, which is rather very easy to handle in a very simple, rapid, surgical management. Objective: the purpose of this study was to evaluate the efficacy of surgical treatment on prepubertal girls with labial adhesions. Methods: A period of 3 years from May 2011 to May 2014 was taken to conduct a study about this condition on prepubertal girls. The place of study was Nepalgunj Medical College, Kohalpur, Banke, Nepal. All patients underwent either outpatient surgical treatment or in operation theatre under short anesthesia, those who were either frightened or non cooperative. They were placed in gynecological (dorsal) position. A thin stainless steel lubricated probe or 1-2 mm. size, Hegar dilator was used to separate the labia minora by firm pressure. Result: All patients were successfully treated and at present they are being followed for recurrence. Conclusion: This benign disorder can be treated by any gynecologist as an office procedure. JNGMC Vol. 12 No. 2 December 2014